2007
DOI: 10.1590/s1413-70542007000300033
|View full text |Cite
|
Sign up to set email alerts
|

Transformações químicas, físicas e enzimáticas de goiabas 'PEDRO SATO' tratadas na pós-colheita com cloreto de cálcio e 1-metilciclopropeno e armazenadas sob refrigeração

Abstract: RESUMOCom o objetivo de estudar o efeito dos tratamentos com cloreto de cálcio e com 1-MCP associando-se a refrigeração, na conservação e qualidade de goiabas Pedro Sato , conduziu-se o experimento em que frutos dessa cultivar foram tratados com solução de CaCl 2 a 2% por 5 minutos e com 1-MCP na concentração de 150 nL/L por 12 horas em câmara hermeticamente fechada. Após os tratamentos, os frutos foram armazenados em câmara refrigerada a 10ºC e 90 ± 2% de umidade relativa, por um período de 25 dias. Os result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 7 publications
(7 reference statements)
3
23
0
9
Order By: Relevance
“…This curious and peculiar behavior agrees with the observations made by Linhares et al (2007), who did not find the polygalacturonase enzyme in the endocarp of guavas but showed that there is high esterase activity in the cell wall. Therefore, it can be inferred that those wall esterases can be responsible for the hydrolysis of crossed bonds among pectin chains and among pectin chains and other polymers liberating the pectin polymers that, by a still unknown process, migrate to the cell interior.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This curious and peculiar behavior agrees with the observations made by Linhares et al (2007), who did not find the polygalacturonase enzyme in the endocarp of guavas but showed that there is high esterase activity in the cell wall. Therefore, it can be inferred that those wall esterases can be responsible for the hydrolysis of crossed bonds among pectin chains and among pectin chains and other polymers liberating the pectin polymers that, by a still unknown process, migrate to the cell interior.…”
Section: Resultssupporting
confidence: 92%
“…However, in guava, PG activity is not found (LINHARES et al, 2007) or is very low, which leads to contradictory and not clearly defined information about the activity of those enzymes regarding the tissue softening of the fruit.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with overestimated values, a total pectin level 7.77% (Table 3) was slightly higher than the expected value of 5.5%; that value is the difference between 14.93% (6.90% + 8.03% Table 1) and 9.42 (general average of the sugars total Table 2). If the correction of the pectin amount (7.77% Table 3) found in the fractions were corrected, the same value would be found (5.5%) and would be higher than the values found in the literature, which are around 2.4% (PAL; SELVARAJ, 1979;MOWLAH;ITOO, 1983;CARVALHO, 1999GIANONNI, 2000;LIMA, 2004;XISTO et al, 2004;VILA, 2007;LINHARES et al, 2007;MENDONÇA et al, 2007;OSHIRO et al, 2008).…”
Section: Resultssupporting
confidence: 52%
“…php?titulo='Goiaba'; http://www.terra.com.br/culinaria/abc/g. htm; http://www.clesio.net/cn/index.php/2008/01/24/as_ frutas_sao_importantes_no_cardapio_de?blog=12), the levels reported in the literature are around 2.4% (PAL; SELVARAJ, 1979;MOWLAH;ITOO, 1983;CARVALHO, 1999GIANONNI, 2000;LIMA, 2004;XISTO et al, 2004;VILA et al, 2007;LINHARES et al, 2007;MENDONÇA et al, 2007;OSHIRO et al, 2008), and with such low levels, the pectins cannot be the only compounds responsible for the guava firmness. Besides, the statement that total pectin levels can remain unaffected, decrease, or increase during the ripening of guava, is inconsistent with the fruit ripening process.…”
Section: Absorption Spectroscopy In the Infrared Region (Ft-ir)mentioning
confidence: 99%